Biodegradable polycaprolactone nanofibres with β-chitosan and calcium carbonate produce a hemostatic effect. (11th August 2017) - Park, Jun-Yong; Kyung, Kyu-Hong; Tsukada, Kosuke; Kim, Sae-Hoon; Shiratori, Seimei
Abstract: We newly developed high-performance blood coagulation nanofibres using Polycaprolactone (PCL) including Calcium carbonate (CaCO3 ) and β-chitosan. The most important feature for a wound dressing is that it is harmless to the human body. Here, we fabricated the nanofibre using all human-safe materials. We used a PCL nanofibre mat as a substrate and then synthesized artificial CaCO3 from sodium carbonate and calcium chloride. The CaCO3 was then added to the fibre solution to create PCL/CaCO3 nanofibres. We coated PCL and PCL/CaCO3 nanofibres with β-chitosan as a hemostatic material via a spray method. For the more uniform coating, we used ultrasonic spray coating method and then compared the blood coagulation abilities of the PCL and PCL/CaCO3 nanofibres. We found that the PCL/CaCO3 nanofibres sprayed with β-chitosan had a greater effect on blood coagulation than the PCL nanofibres. In the result of animal experiment, β-chitosan have a key role in changing of surface wettability from hydrophobic to hydrophilic. Moreover, this is contributed to enhance blood coagulability. PCL/CaCO3 nanofibres sprayed with β-chitosan therefore offer promise in medical applications. Graphical abstract: Highlights: The materials which used to fabricate nanofibre were all human-safety. β-chitosan had a key role in changing of PCL surface wettability from hydrophobic to hydrophilic. The presence of CaCO3 was determined blood clotting rate. PCL/CaCO3 nanofibre sprayed with β-chitosan exhibited highest blood clotting ability.